Analysis of Constitutional Court Decision No. 16/PUU-XVIII/2020 Regarding the Honorary Council's Approval of Summoning a Notary in the Examination of Criminal Cases - Taufiqsyah, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In writing this journal the author discusses legal issues regarding the Analysis of the Constitutional Court Decision Number 16/PUU-XVIII/2020 concerning the Approval of the Honorary Notary Council for Summoning Notaries in the Examination of Criminal Cases. The Constitutional Court (MK) stated that it did not accept and rejected the judicial review of Article 66 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions regarding the examination of Notaries in the judicial process with the approval of the Notary Honorary Council ( MKN). The Petitioners argue that the phrase with the approval of the Notary Honorary Council in Article 66 of the Law on the Position of Notaries places the Notary Honorary Council as having absolute and final authority to approve or disapprove a notary's summons to attend a case examination. This means that investigators, public prosecutors and judges cannot take further legal action if the Notary Honorary Council does not give their approval. With the Constitutional Court's decision issued by the Constitutional Judge regarding Article 66 paragraph (1) of the Notary Law, a problem arises regarding the basis of the judge's consideration of the Constitutional Court's decision regarding the Honorary Council's approval of the summons of a Notary in the examination of criminal cases. The approval of the Notary Honorary Council in granting permission to the parties to take or notarize and examine the Notary remains valid. The Constitutional Court (MK) stated that it did not accept and rejected the material review requested by the Indonesian Prosecutors Association.